1999
DOI: 10.1103/physrevlett.82.4992
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Two-Pion Exchange and Proton-Proton Partial-Wave Analysis

Abstract: The chiral two-pion exchange component of the long-range pp interaction is studied in an energydependent partial-wave analysis. We demonstrate its presence and importance and determine the chiral parameters c i (i 1, 3, 4). The values agree well with those obtained from pion-nucleon amplitudes.[S0031-9007(99)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
265
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(284 citation statements)
references
References 49 publications
18
265
1
Order By: Relevance
“…On the other hand, the reliability of the long distance chiral interaction does not depend on how the short distance unknown interaction is organized. This has been proven by the first chiral potential fits by the Nijmegen group from their pp [6] and np + pp [8] analyses and more recently verified with increased statistics by the Granada group [11]. This leaves open the possibility that better fits than those found here should be possible by properly altering the short distance structure.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…On the other hand, the reliability of the long distance chiral interaction does not depend on how the short distance unknown interaction is organized. This has been proven by the first chiral potential fits by the Nijmegen group from their pp [6] and np + pp [8] analyses and more recently verified with increased statistics by the Granada group [11]. This leaves open the possibility that better fits than those found here should be possible by properly altering the short distance structure.…”
Section: Discussionmentioning
confidence: 76%
“…[2] for an early review) and, after many years, culminated in the admirable Nijmegen partial wave analysis (PWA) of 1993 [3], based on the crucial observations that charge-dependent one-pion-exchange (CD-OPE), tiny but essential electromagnetic and relativistic effects, and a judicious selection of the scattering database could actually provide a satisfactory fit with χ 2 /datum ∼ 1 for a total number of data consisting, as of 1993, of 1787 pp and 2514 np (normalizations included) at the 3 σ level. These criteria have set the standard for PWA's and the design of high quality phenomenological potentials [4][5][6][7][8][9][10][11][12]. The inference point of view is mainly phenomenological and requires a balanced interplay between which data qualify as constraints and which models provide the most likely description of the data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix elements ψ|Ô|ψ should then incorporate the consequences of chiral-symmetry breaking in a model-independent way. Calculations have shown that the NN phase shifts can be understood, and deuteron bound-state static properties reliably computed, with NN potentials derived from χPT [7,8,9,10,11]. This is now a sophisticated enterprise, with N 3 LO [O(P 4 )] potentials recently having been obtained [11,12,13].…”
Section: Deuteron Wave Functionsmentioning
confidence: 99%
“…There exists also a determination of this parameter from the NN data by the Nijmegen group. They report c 3 = −5.08 ± 0.28 GeV −1 in their 1999 pp analysis [ 24] and c 3 = −4.78 ± 0.10 Table 4 Low-energy parameters. c i are given in units of GeV −1 andd i in units GeV −2 .…”
Section: The Low-energy Constantsmentioning
confidence: 99%